Physics and national socialism : an anthology of primary sources - Hentschel, Klaus 1961- Hrsg (Modern Birkhäuser classics, 2011)
1. Aim and general description of the anthology -- 2. Notes on the historiography of National Socialism -- 3. The impact of Nazi science policy on physics instruction and research -- 4. Emigration research -- 5. Physics in Nazi Germany -- 6. Style and rhetoric -- 7. The text -- I. Controversies prior to 1933 -- II. After the Nazi seizure of power -- III. The ideological schism, 1936-1939 -- IV. Physics at war, 1939-1945 -- V. The legacy of National Socialism -- Appendix